2020
DOI: 10.1186/s40659-020-00316-0
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin inhibits proliferation and inflammatory response in human HaCaT keratinocytes and ameliorates imiquimod-induced psoriasis-like skin lesion in mice

Abstract: Background Psoriasis is a common chronic inflammatory skin disease. Keratinocytes hyperproliferation and excessive inflammatory response contribute to psoriasis pathogenesis. The agents able to attenuate keratinocytes hyperproliferation and excessive inflammatory response are considered to be potentially useful for psoriasis treatment. Daphnetin exhibits broad bioactivities including anti-proliferation and anti-inflammatory. This study aims to evaluate the anti-psoriatic potential of daphnetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…In this study, M5 stimulation could induce NF-κB activation in HaCaT cells by increasing the p-IKK level, decreasing the IκB-α level in the cytoplasm, and increasing NF-κB p65 nuclear translocation, which was recovered by pretreatment with coptisine, suggesting that the anti-inflammatory effects of coptisine could be mediated by regulating the NF-κB pathway. These findings concur with a previous study reporting that daphnetin, a natural compound from Daphne odora, reduced M5-induced inflammation in HaCaT cells by inhibiting the NF-κB signaling pathway activation [56].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, M5 stimulation could induce NF-κB activation in HaCaT cells by increasing the p-IKK level, decreasing the IκB-α level in the cytoplasm, and increasing NF-κB p65 nuclear translocation, which was recovered by pretreatment with coptisine, suggesting that the anti-inflammatory effects of coptisine could be mediated by regulating the NF-κB pathway. These findings concur with a previous study reporting that daphnetin, a natural compound from Daphne odora, reduced M5-induced inflammation in HaCaT cells by inhibiting the NF-κB signaling pathway activation [56].…”
Section: Discussionsupporting
confidence: 93%
“…The treatment of psoriasis is a challenge because of its pathogenic complexity ( Greb et al, 2016 ; Dainichi et al, 2018 ). Some potential drugs and methods for the treatment of psoriasis were proposed in some studies recently ( Hawkes et al, 2017 ), among which Daph showed a good symptom relief effect in the mouse psoriasis model ( Gao et al, 2020 ). However, during the onset of psoriasis, Daph does not penetrate the thickened epidermis readily, making it difficult to reach the subcutaneous layer.…”
Section: Discussionmentioning
confidence: 99%
“…Daphnetin (7,8-dihydroxycoumarin) is isolated from Daphne Korean Nakai and used for cancer and inflammatory disease treatment because of its antiproliferation and anti-inflammation effects ( Pei et al, 2021 ). Previous research has shown the therapeutic effectiveness of Daph (in a cream form) in a psoriasis mouse model ( Gao et al, 2020 ). Daph was reported to inhibit the abnormal proliferation of keratinocytes by inhibiting the NF-κB signaling pathway, thus reducing the release of inflammatory factors and alleviating the symptoms of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…M5 ((IL-1α, IL-17A, IL-22, oncostatin M, and TNF-α) can induce keratinocytes to exhibit some of the characteristics of psoriatic keratinocytes in vitro [ 16 ]. Meanwhile, it has been reported that IL-17 and IL-22 enhance cutaneous inflammation, leading to epidermal thickening of psoriatic lesions and adherence of psoriatic scales [ 17 ].…”
Section: Introductionmentioning
confidence: 99%